Citizen participation in building citizen-centric smart cities - Lim, Sengboon; Jalaluddin Abdul Malek; Mohd Yusof Hussain; Zurinah Tahir (Penerbit Universiti Kebangsaan Malaysia, 2018)
Recently, the governors of technology-driven smart cities have been criticised for ignoring their citizens and limiting the role of the general public to being passive users. Even though the goal of realising citizen centricity has been embodied in the visions of most smart cities, it has remained to be a rhetorical notion. This paper was aimed to understand the citizen participation and citizen centricity phenomena in smart cities. The research method of this review paper applied the literature review framework of vom Brocke et al., with modification. Salient features such as the domains of smart cities, state of citizen centricity, Arnstein’s ladder of participation, characteristics of the citizens, and management of the associated challenges have been elaborated in this theoretical study. It is postulated that citizen and participation factors are essential to build the citizen-centric smart cities. This proposition includes the characteristics of citizens and co-production, whereby the former encompasses the behaviours and roles of the citizens, while the later entails the engagement of citizens in the upper level of public within the rungs of partnership and delegated power, building of trust-capacity relationships between public professionals and citizens, as well as understanding of deliberative democracy. This research agenda will serve as a basis for further empirical research.